(untitled) - Ozer, Jan (Indianapolis, IN, 2004)
Guide provides everything you need to know about digital video, such as which camera to choose and why, how to shoot the best footage, how to capture the best sound, how to get the video from the camera to a computer, and more.
Keywords: Digital video,Video recording,DVDs,DVD,Phim kỹ thuật số,Ghi hình; Design and construction,Thiết kế và dàn dựng